The Influence of Store Atmosphere, Brand Awareness, and Lifestyle on Fashion Purchase Decisions at Kobapa Store, Delitua District - Reika Dasha Mihwa; Arief Hadian; Yayuk Yuliana; Mutawaqil Bilah Tumanggor (International Journal of Economics, Commerce, and Management, 2026)
This research aims to examine the influence of store atmosphere, brand awareness, and lifestyle on purchasing decisions at Kobapa Store in Delitua District. This study uses a quantitative research method with a questionnaire research design. The subject of this research is the products of Kobapa Store, and the object of the study is consumers who purchase products at Kobapa Store, totaling 97 respondents. Data collection techniques include observation, questionnaires, and documentation. Data analysis techniques involve validity tests, reliability tests, and classical assumption tests. The data analysis method used is multiple linear regression with the assistance of SPSS 25 software. The t-test results show that store atmosphere has a positive effect on purchasing decisions. Brand awareness has a positive effect on purchasing decisions. Lifestyle also influences purchasing decisions. The F-test results indicate that store atmosphere, brand awareness, and lifestyle simultaneously affect purchasing decisions at Kobapa Store in Delitua District, with an F calculated value of 4.141 > F table value of 2.700, and a significance value of 0.008 < 0.05. The adjusted coefficient of determination (R Square) is 0.338, meaning that 33.8% of the dependent variable can be explained by the independent variables, while the remaining 66.2% is explained by other variables outside the ones studied.